Reversible photochromism and photoluminescence modulation in (K,Na)NbO3‐based ceramics via oxygen vacancy regulation - Yang, Bin; Zhang, Tao; Zhang, Hejin; Irshad, Muhammad Sultan; Guo, Jinming (Journal of the American Ceramic Society, 2025)
Most of the optical behaviors in photoelectric multifunctional ceramics strongly depend on the addition of rare‐earth elements. However, the limited species of rare‐earth cations available as luminescence centers restrict the further development of photoelectric devices. Additionally, introducing the large atomic‐radii elements usually dramatically deteriorates the piezoelectric properties. Herein, the novel photochromism and luminescence modulation properties have been realized in CuO‐doped [(K0.43Na0.57)0.94Li0.06][(Nb0.94Sb0.06)0.95Ta0.05]O3 (KNLNST) piezoelectric ceramics which show intense sensitivity to visible‐light irradiation. As a strategy for regulating oxygen vacancy concentrations in piezoelectric ceramics, different CuO amounts are doped to generate color centers for photochromism. The photoluminescence phenomenon exhibiting green emission under 375 nm excitation is observed in KNLNST piezoelectric ceramics, which is most commonly realized via rare‐earth doping in luminescent materials. KNLNST–0.3CuO ceramics with the highest oxygen vacancy concentration achieve a reversible luminescence modulation of 46.9% by altering light irradiation and thermal stimulus. Moreover, a hand‐rewritable optical information test demonstrates exceptional reproducibility and fatigue durability. This research displays the controllable photochromism and luminescence behaviors in ceramics via regulating oxygen vacancy concentration by CuO “hard” doping. The lead‐free high performance photoelectric ceramics fulfill the demands of potential applications in anti‐counterfeiting and optical storage devices. The presence of vacancies at A‐sites and oxygen vacancies via iDPC‐STEM images, and various types of programmable letters (V, T, I, and so on), different shapes about anti‐counterfeiting patterns on the surface of KNLNST–0.3CuO ceramics under irradiation with realizing a reversible optical data storage based on “0”, “1” logic codes.